Vietnamese herbal opioid addiction treatment medication Heantos-4 - Turkia, Mika (Journal of Medicinal Herbs and Ethnomedicine, 2024)
Heantos-4 is a non-toxic, non-addictive herbal detoxification medicine for opioid addiction. It was initially invented in Vietnam in the 1980s and tested and developed further in Vietnam in the early 1990s. Since 1995 it has been studied in international cooperation, standardized first into earlier versions and finally to the current version Heantos-4. The various versions have been utilized at Vietnamese inpatient rehabilitation clinics since 1991. During detoxification, it has a predominantly sedative effect. It likely acts as a dopaminergic stabilizer, counteracting both hyperdopaminergic and hypodopaminergic states. Up to 2008, an estimated 9000 patients had been treated. An uncontrolled phase III clinical trial carried out in Vietnam in 2008 indicated an approximately 90% success rate during an initial seven-day inpatient detoxification treatment. This formally unpublished trial is briefly reviewed in this article. In 2012, Heantos-4 was licensed for over-the-counter outpatient use in Vietnam. The Heantos-4 formulation consists of extracts of twelve plants commonly used in Traditional Chinese Medicine (TCM). In addition, animal-based gelatin is utilized as a binding agent. The product has been said to conform to Good Manufacturing Practices (GMP) standards. The patent of the product belongs to the National Institute of Chemistry of the Vietnam Academy of Science and Technology (VAST). An initial hindrance to clinical trials and international adoption was a lack of necessary polypharmacokinetic methods for determining the constituent molecules and the active agents of the complex mixture. In 2020 a key active agent l-tetrahydropalmatine (l-THP) was identified. Due to synergistic effects between components Heantos-4 likely provides better tolerability and a greater therapeutic efficacy in comparison to l-THP alone. The article also briefly describes the approximately 40-year history of the development of Heantos, partly based on unpublished internal documents of the United Nations Development Programme (UNDP). In the 2000s, a severe opioid epidemic emerged in the United States. More than ever an effective method for resolving opioid addiction is needed. As of yet only uncontrolled clinical trials of Heantos have been carried out. There is thus an urgent need for randomized controlled clinical trials.